Quel équilibre entre urbanisation et préservation des espaces agricoles périurbains ? Le cas d’une agglomération moyenne - José Serrano (Développement Durable et Territoires)
Where is the balance between a town growth and the protection of agricultural per urban spaces ? The case of an average developed area. Urban sustainable development is in opposition with urban spraw. Today, elected officials speak big about the application of sustainable development principles. They are looking for preserving the setting and for controling the urban expansion. Nethertheless, the same elected officials create ambitious projects in urban planning documents. Through the analysis of elected officials developement projects, we’ll try to determine the importance of protecting natural spaces. The second objective is to know which are the conditions to recognize agricultural and natural spaces as an extention of the town (and not as the lack of it). Our hypothesis is that the recognition of farm land and natural spaces depends on a modification of the perception of the farmers’ role. But facing the extend of change regarding this evolution the intervention of a mediator is mandatory